Gut Dysbiosis Is Associated With the Severity of Cryptogenic Stroke and Enhanced Systemic Inflammatory Response - Zheng, Qianyi; Chen, Yongkang; Zhai, Yanping; Meng, Lin; Liu, Han; Tian, Haiyan; Feng, Renyi; Wang, Jiuqi; Zhang, Rui; Sun, Kedi; Gao, Lina; Wang, Yijing; et al. (Frontiers in Immunology, 2022)
Studies implicate that gut pathological changes are associated with many neurological diseases. However, whether these changes happened and their potential association with the progress of the disease in cryptogenic stroke (CS) have not been elucidated yet. In this study, a high prevalence of gastrointestinal (GI) dysfunction and gut inflammation with increased intestinal permeability have been found in CS patients. The systemic inflammation in CS patients was also found by measuring levels of plasma C-reactive protein (CRP), lipopolysaccharide (LPS), LPS binding protein (LBP), and white blood cells (WBC) count. To find the cause of GI dysfunction and gut inflammation, using 16S rRNA sequencing, we found intestinal microbiota disturbance with increased alpha diversity. Compared to controls, there is a higher abundance of Enterobacteriaceae, Streptococcaceae, and Lactobacillaceae at the family level, and Escherichia-Shigella, Streptococcus, Lactobacillus, and Klebsiella at the genus level in CS patients. Our results showed that not only gut inflammatory but also the abundance of Klebsiella, Escherichia-Shigella, and Bacteroides were associated with the level of systemic inflammation. Moreover, we found that both of level of systemic inflammation and the abundance of Klebsiella rather than Escherichia-Shigella or Bacteroides are correlated with NIHSS scores and infarct volumes. In conclusion, our results suggest that imbalanced intestinal homeostatic and systemic inflammatory reactions were correlated with gut dysbiosis in CS patients, more importantly, we found that alteration of gut microbiota is associated with the severity of CS.